New Insights about Antibiotic Production by Pseudomonas aeruginosa: A Gene Expression Analysis - Gionco, Bárbara; Tavares, Eliandro R.; de Oliveira, Admilton G.; Yamada-Ogatta, Sueli F.; do Carmo, Anderson O.; Pereira, Ulisses de Pádua; Chideroli, Roberta T.; Simionato, Ane S.; Navarro, Miguel O. P.; Chryssafidis, Andreas L.; Andrade, Galdino (Frontiers in Chemistry, 2017)
The bacterial resistance for antibiotics is one of the most important problems in public health and only a small number of new products are in development. Antagonistic microorganisms from soil are a promising source of new candidate molecules. Products of secondary metabolism confer adaptive advantages for their producer, in the competition for nutrients in the microbial community. The biosynthesis process of compounds with antibiotic activity is the key to optimize their production and the transcriptomic study of microorganisms is of great benefit for the discovery of these metabolic pathways. Pseudomonas aeruginosa LV strain growing in the presence of copper chloride produces a bioactive organometallic compound, which has a potent antimicrobial activity against various microorganisms. The objective of this study was to verify overexpressed genes and evaluate their relation to the organometallic biosynthesis in this microorganism. P. aeruginosa LV strain was cultured in presence and absence of copper chloride. Two methods were used for transcriptomic analysis, genome reference-guided assembly and de novo assembly. The genome referenced analysis identified nine upregulated genes when bacteria were exposed to copper chloride, while the De Novo Assembly identified twelve upregulated genes. Nineteen genes can be related to an increased microbial metabolism for the extrusion process of exceeding intracellular copper. Two important genes are related to the biosynthesis of phenazine and tetrapyrroles compounds, which can be involved in the bioremediation of intracellular copper and biosynthesis of the organometallic compound. Additional studies are being carried out to further prove the function of the described genes and relate them to the biosynthetic pathway of the organometallic compound.